„Ne szavazz, csináld magad!”: Gondolatok a taxisblokádról - Pál, Gabriella (Szociológiai Szemle, 2024)
The events referred to as the ‘taxi drivers blockade’ occurred in Hungary between October 26th and 28th of 1990. The blockade not only interfered with the regular activities of the general populace, the police, and the politicians, but showed itself to be a provocative topic for sociological and political analysis. The paper seeks to locate the confluence of circumstances and conditions which made this activity possible. According to M. Olson’s analysis large latent groups are unable to act in accordance to their common interest under ordinary circumstances. Starting from the theory of collective action, i.e., assuming that the group members were rational actors, the paper explains the rapid growth and success of the taxi drivers using two basic factor clusters: (1) the group characteristics of the taxi drivers, such as an excellent inner communication channel, repeated and successful previous actions, their mutual dependence, and the costliness of the free rider’s alternative; (2) the social ramifications of their actions, i.e., the tactics of the government and the sympathy of individuals outside of the group. The support of outsiders meant both protection and significant constraint: exclusive entrepreneurial interests could not be voiced in the face of relatively broad civil support and the general expectations of the disobedience movement.